Fraud prevention: issues and recommendations - Muhammad, Nurul Syafiqah Ros; Azis, Saflina; Kamal, Mustafa (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Financial fraud remains a serious and persistent threat to organisations, involving the intentional manipulation of financial information for personal gain or to mislead stakeholders. Despite technological and accounting advancements, many companies still struggle with effective prevention, leading to financial losses, reputational damage, and weakened long-term sustainability. Preventing fraud requires not only robust systems and policies but also strong organisational culture, proper oversight, and heightened employee awareness, as weaknesses in these areas create opportunities for misconduct.